The evolution of Σ3 grain boundaries in the strip-cast Hi-B grain orientated Fe-6.5% Si alloy. (15th April 2021) - Zhang, Yuanxiang; Yuan, Guo; Wang, Yang; Fang, Feng; Zhang, Weina; Zhang, Xiaoming; Wang, Guodong
Abstract: A novel high magnetic induction Fe-6.5%Si alloy with B800 that reached up to 1.77 Telsa was prepared by twin-roll strip casting. Electron backscattered diffraction (EBSD) investigations demonstrated that Σ3 grain boundaries formed in the body-centered cubic (BCC) metal solidified microstructure without phase transition where the ratio of grain boundaries was greater than 20%. Transmission electron microscopy (TEM) revealed that the partial Σ3 grain boundaries are BCC structured twinning. A certain amount of Σ3 boundaries were inherited from the process of warm rolling, cold rolling and annealing, which acted to stabilize the matrix grain boundaries, resulting in the formation of a perfect Goss microstructure with excellent magnetic properties. Graphical abstract: Image, graphical abstract